ANALISIS KINERJA SALURAN SEKUNDER IRIGASI WAY PAMALI KECAMATAN LOLONGGUBA KABUPATEN BURU - Mohammad Gazaly Tuanany; Isak Lilipory; Willem Gaspersz (Journal Agregate, 2023)
An efficient and effective irrigation canal management system greatly influences the distribution of water to the surrounding community and the agricultural sector. To maintain it, periodic maintenance and evaluation is required so that the physical condition of irrigation structures continues to function optimally. For this reason, this study aims to assess the performance of the Way Pamali secondary irrigation canal, Lolongguba District, Buru Regency, Maluku Province. This research uses PU Regulation No. 12/PRT/M/2015 as a guideline for data analysis. While the research data was obtained through direct field surveys by assessing the physical condition of irrigation construction buildings and the surrounding area. The results showed that there was damage to the wall and floor of the canal on the Left Section (BA.Ki) 4 and the Left Section (BA.Ki) 6. The results of the performance index assessment of the carrier channel infrastructure were 59.80% on sections Ba.Ki.4 and of 57.05% on section Ba.Ki.6 with the title of "bad" Physical Infrastructure of the Carrier Channel (Secondary Channel). The total funds required for the rehabilitation of the physical irrigation structures are Rp. 2,486,731,000.- (two billion four hundred eighty six million seven hundred thirty one thousand rupiah).